Removal of multiwalled carbon nanotube contaminants from surfaces with microscale topological features. Issue 1 (29th June 2015) - Karimi, Zahra; Su, Paul; Hassan, Syed; Haghpanah, Babak; Doerr, William; Vaziri, Ashkan
Abstract : Experiments were performed to examine the efficiency of surfactants to remove multi‐walled carbon nanotubes (MWCNTs) from silicon substrates with nano and microscaled features. In the first set of experiments, nanoscale features were induced on silicon wafers using SF6 and O2 plasma. In the second set, well‐defined microscale topological features were induced on silicon wafers using photo lithography and plasma etching. The etching time was varied to create semi‐ellipsoidal pits with average diameter and height of ∼7–9 µm, and ∼1–3 µm, respectively. For the cleaning process, the MWCNTs were wiped off using a simple wiping mechanism by two different surfactants and distilled water. The areal density of the MWCNTs was quantified prior to and after the removal using scanning electron microscopy (SEM) and post‐image processing. For a surface featured with nanoscale asperities, the removal efficiency was measured to be in the range 83–99% based on substrate type and surface roughness. No evident relationship was observed between the etching time and the removal efficiency. For surfaces with microscale features, increasing the etching time results in appearance of larger pits and significant decrease in the removal efficiency. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 161–168, 2016